2012
DOI: 10.3109/00498254.2012.727499
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies variation in the metabolism of zoniporide by aldehyde oxidase

Abstract: 1. Aldehyde oxidase (AO) is a cytosolic enzyme that contributes to the Phase I metabolism of xenobiotics in human and preclinical species. 2. Current studies explored in vitro metabolism of zoniporide in various animal species and humans using S9 fractions. The animal species included commonly used pharmacology and toxicology models and domestic animals such as the cat, cow or bull, pig and horse. 3. In addition, gender and strain differences in some species were also explored. 4. All animals except the dog an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 56 publications
4
31
0
Order By: Relevance
“…Beedham et al (1987) showed monkey hepatic cytosol to have the highest AOX activity with N-heterocyclic compounds. However, recent results by Dalvie et al (2013) indicate that zoniporide intrinsic clearance by rhesus monkey S9 is low when compared with humans and guinea pigs. The molecular basis for these species and substrate differences are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Beedham et al (1987) showed monkey hepatic cytosol to have the highest AOX activity with N-heterocyclic compounds. However, recent results by Dalvie et al (2013) indicate that zoniporide intrinsic clearance by rhesus monkey S9 is low when compared with humans and guinea pigs. The molecular basis for these species and substrate differences are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Rhesus monkey would require more compound for dosing (the rhesus monkey typically weighs 6 to 10 kg, whereas the cynomolgus monkey weighs 3 to 5 kg), is more expensive, and is a less often used species for conducting routine pharmacokinetic and toxicokinetic studies. Dalvie et al, 2013 …”
Section: Discussionmentioning
confidence: 99%
“…The second step was found to be mediated by both guinea pig AO and cow XO (Rashidi et al, 2007). Given that many studies have shown that animal models are poor predictor of molybdenum oxidase activity we decided to explore the in vitro metabolism with human XO and AO (Sahi et al, 2008;Choughule et al, 2013;Dalvie et al, 2013). We initially explored the time course of 6MP metabolism by monitoring the production of the intermediate 6TX and the final product 6TUA in pooled human liver cytosol.…”
Section: Resultsmentioning
confidence: 99%
“…One caveat to bear in mind is that all of these in vitro experiments were performed using AO/XO from nonhuman sources. Major species differences have already been reported for several compounds metabolized by AO and hence extrapolation of pharmacokinetic data from other mammalian species to humans is not advisable (Choughule et al, 2013;Dalvie et al, 2013). Moreover, mammalian xanthine oxidoreductase (XOR) exists in two interconvertible forms, xanthine oxidase (XO) and xanthine dehydrogenase (XDH).…”
mentioning
confidence: 99%